Impact of thunderstorm activities on tropospheric NOx adversely affecting the climate change over Bagmati province of Nepal - Sharma, Shriram; Regmi, Nabaraj; Neupane, Sujan (Scientific World, 2023)
Lightning is a complex electrical discharge that occurs in the atmosphere. Huge currents associated with the lightning discharge raises the ambient temperature resulting in the change in atmospheric chemistry. The extreme temperatures within lightning channels break apart molecular nitrogen (N2) and oxygen (O2) to produce nitrogen oxides (NOx). NOx act as indirect greenhouse gases by producing the tropospheric Ozone. Likewise, NOx gases also affect the global greenhouse gas budget through the change in concentration of hydroxyl radical (OH) and Methane. This study analyzes the association of lightning stroke density with the tropospheric NOx over the Bagmati province (central region) of Nepal, during pre-monsoon and post-monsoon for 3 years (2018 to 2020). The tropospheric NOx was examined by utilizing the data from Ozone Monitoring Instrument (OMI), whereas the lightning stroke data was obtained from VAISALA’s Global Lightning Detection (GLD-360) Network. The lightning stroke density for each season were plotted against the corresponding average value of NOx to obtain the correlation coefficient over the period of study. Strong positive correlations between lightning and NOx production during per-monsoon periods were obtained for all the three years of study period, whereas, comparatively weak correlations are obtained for the post-monsoon seasons. Nevertheless, the NOx production due to lightning is found to be strong, during the pre-monsoon period, a relatively dry season over the Bagmati province. This clearly indicates that lightning is a big source of tropospheric NOx,that in turn produces greenhouse gases and hence contributes to the climatic changes over the central region on Nepal.